THE MANIFESTATION OF SOCIAL RESPONSIBILITY IN AGRICULTURE - Matei, Mirela; Done, Ioan (Economics of Agriculture, 2011)
Social responsibility (SR) is a new concept that guides not only the activity of transnational corporations but also the actions of small and medium-sized enterprises, portfolio investors and farmers. All businesses must act responsibly, in addition to the objective motivation of maximizing the proft, they must follow the intensifcation of the positive effects they have on the environment, consumers, employees and community. In other words, businesses must deliberately pursue the public interest and, through their actions, they must focus on the three Ps: people, planet and proft. Despite the pro and con opinions on the social responsibility of businesses, they are increasingly involved in society and their efforts are supported by international organizations, local public authorities or by various institutions that either initiated various partnerships, or developed CSR principles that can be adopted voluntarily or had various legislative initiatives.